Penggunaan Media Pembelajaran Interaktif dan Games Kahoot pada Materi Limit di Masa New Normal - Isti Kamila; Mulyati Mulyati; Ani Andriyati; Embay Rohaeti; Maya Widyastiti (Pelita: Jurnal Pengabdian kepada Masyarakat, 2022)
The partner involved in this community service activity is MA Al Falak. The devotion is to provide limit material by using interactive learning media and kahoot games to give a positive influence on the mastery of the concept of limit students of MA Al Falak. The implementation of devotion to the SCHOOL MA Al Falak carried out three stages. First, the provision of pretest, materials and kahoot games. The second, divide the class into two groups to get intensive guidance from two students involved in this PKM. Third, review of the material and the provision of posttest. The results of the implementation of this devotion based on the results of descriptive statistical calculations, there was an increase in student learning outcomes that can be seen from the average student pretest score of only 34.35 then increased to 78.70.